Management Of Teba Majelangu As Educational Tourism in Denpasar City - Suwitra Wirya, I Made; Wisnawa, I Made Bayu; Widiantara, I Gusti Agung Bagus (Akademi Komunitas MAPINDO, 2024)
One of the natural, cultural and educational tourist attractions of Denpasar City is Subak TeBA MajelanguEducational Tourism. However, the number of tourists who come to this place is still very low compared toother tourist attractions in Denpasar City. Thus, the manager must make efforts to develop a strategy so thatthe attraction of Subak TeBA Majelangu Educational Tourism becomes an educational tourist attraction in thecity of Denpasar in the most effective way. Therefore, the purpose of this article is to find out the strategies thatare carried out so that Subak TeBA Majelangu Educational Tourism becomes a better educational touristattraction in the city of Denpasar, as well as the efforts made by managers to develop this strategy. This studyused a qualitative research approach involving data collection through observation, interviews anddocumentation. Data collected at the research location through the process of analyzing data, describing thedata and continued with drawing conclusions. The results showed that the Village-Owned Enterprise(BUMDES) of Kesiman Majelangu Village and the Tourism Awareness Group (POKDARWIS) manage theoperations of Subak TeBA Majelangu Educational Tourism which is directly responsible to the villagegovernment. Furthermore, Subak TeBA Majelangu Educational Tourism requires the right strategy to developit. This strategy can include developing tourism products, increasing security, increasing the potential thatcharacterizes Subak TeBA Majelangu Educational Tourism and developing infrastructure and facilities.Keywords: Subak, Educational Tourism, management strategy, management efforts